Low Dose BMP2-Doped Calcium Phosphate Graft Promotes Bone Defect Healing in a Large Animal Model - Liu, Tie; Fang, Wen; Wu, Gang; Li, Yining; Pathak, Janak L.; Liu, Yuelian (Frontiers in Cell and Developmental Biology, 2021)
Background: Bone grafts are in high demand due to the increase in the cases of bone defects mainly caused by trauma, old age, and disease-related bone damages. Tissue-engineered calcium phosphate (CaP) biomaterials match the major inorganic contents of bone, thereby could be the potential bone graft substitute. However, CaP-bone grafts lack the osteoinductivity that is vital for effective bone regeneration. In this study, we aimed to test the bone defect healing potential of biomimetically fabricated low dose BMP2-doped CaP (BMP2.BioCaP) grafts in a large animal model. Methods: Low dose BMP2 was doped internally (BMP2-int.BioCaP) or on the surface of CaP (BMP2-sur.BioCaP) grafts during the fabrication process. Our previous study showed the robust bone regenerative potential of BMP2-int.BioCaP and BMP2-sur.BioCaP grafts in the rat ectopic model. In this study, we investigated the bone defect healing potential of BMP2.BioCaP grafts in sheep humerus/femoral defects, as well as compared with that of autologous bone graft and clinically used deproteinized bovine bone (DBB) xenograft. Results: Different ways of BMP2 doping did not affect the surface morphology and degradation properties of the graft materials. Micro-CT and histology results showed robustly higher bone defect-healing potential of the BMP2.BioCaP grafts compared to clinically used DBB grafts. The bone defect healing potential of BMP2.BioCaP grafts was as effective as that of the autologous bone graft. Although, BMP2-int.BioCaP doped half the amount of BMP2 compared to BMP2-sur.BioCaP, its’ bone defect healing potential was even robust. The BMP2.BioCaP grafts showed less immunogenicity compared to BioCaP or DBB grafts. The volume density of blood vessel-like and bone marrow-like structures in both BMP2.BioCaP graft groups were in a similar extent to the autologous group. Meticulous observation of higher magnification histological images showed active bone regeneration and remodeling during bone defect healing in BMP2.BioCaP graft groups. Conclusion: The robust bone regenerative potential of BMP2.BioCaP grafts in the ectopic model and in-situ bone defects in small and large animals warrant the pre-clinical studies on large animal critical-sized segmental bone defects.